2011
DOI: 10.1002/gps.2724
|View full text |Cite
|
Sign up to set email alerts
|

Instruments for comprehensive needs assessment in individuals with cognitive complaints, mild cognitive impairment or dementia: a systematic review

Abstract: Even though a wide range of needs assessment instruments is available, most instruments assess the needs of individuals with subjective cognitive impairment, mild cognitive impairment and dementia on a general level rather than on a more concrete level that may serve better to inform interventions for this growing population. In addition, we suggest basing the development of instruments firmly on an adequate theoretical framework and standardised procedural guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 56 publications
0
24
0
2
Order By: Relevance
“…A previous systematic review conducted in 2012, has provided an overview of the existing needs assessment instruments among people with cognitive impairment [26], but no such studies have been conducted considering the need assessment of their informal caregivers.…”
Section: Introductionmentioning
confidence: 99%
“…A previous systematic review conducted in 2012, has provided an overview of the existing needs assessment instruments among people with cognitive impairment [26], but no such studies have been conducted considering the need assessment of their informal caregivers.…”
Section: Introductionmentioning
confidence: 99%
“…As the complete breakdown of developmental stabilization, illustrated by the number of individuals with clinical symptoms across the lifespan, is more rare than the successful stabilization, we argue that it would be productive for aging research in general to distinguish between lifespan developmental research focusing on predictors of both positive and negative destabilization (i.e., gains and losses) and lifespan developmental research focusing on predictors of stabilization. Whereas the first may identify single or accumulative risk and protective factors and may lay the groundwork for early detection and prevention (e.g., Eschen, Martin, Schreiter Gasser, & Kliegel, 2009;Schmid, Eschen, Rüegger-Frey, & Martin, 2012), the second must have a concept of and can empirically test the essential elements and longitudinal short-term within-person dynamics of the longer-term stabilization of a particular goal function, thus laying the groundwork for truly maintaining higher-order functions across the lifespan. Generally speaking, whenever a higher-order function is potentially stabilized through the dynamic engagement of two or more nonlinear dynamic systems and the level of the goal function feeds back into the regulation of the nonlinear dynamic systems, the functional approach can potentially be applied.…”
Section: Functional Approaches To Lifespan Development In Psychologymentioning
confidence: 99%
“…One research study examining the needs of older people with severe mental illness including dementia, found that most (70%) people were not receiving the interventions indicated by their assessed needs (Cummings & Kropf, 2009). This may be due to the assessed needs not being specific enough to link to particular interventions (Schmid, Eschen, R€ uegger-Frey, & Martin, 2012), for example, mobility needs may require physiotherapy or wheelchair repair services. Alternatively, this may result from a failure to develop services that meet the needs of people with dementia (Knapp et al, 2007).…”
Section: Introductionmentioning
confidence: 99%